Restructuring of spatial relations of business services in metropolitan regions - a research project - Petra Jähnke (European Regional Science Association (ERSA), 2002)
The present urban-economic and spatial- functional changes in metropolitan regions are both, the outcome of a restructuring process induced by ICT-technologies in all economic sectors, as well as the consequences of globalisation and the growing importance of the tertiary sector at the end of the 20th century. The process of chance in metropolitan regions in conjunction with the question about the production and structure of a new metropolitan type is discussed in the "global-city" research. Nowadays, services are seen to have an own, separate effect on spatial structure. Especially the producer-orientated services, which are very differently distributed in metropolitan regions, have become the decisive criteria for economic success due to their productivity. Important factors in agglomerations are: proximity to customers and to high-level infrastructure, as well as the potential disposal over specific urban relocation conditions and soft regional relocation factors. Apart from that, spatial differences in the relocation profiles in the service economy can be put down to the distinction into back offices, simple to medium, highly requested as well as highly specialised, and international services. Are these spatial-functional classifications adequate, nowadays? Our economy and society has become increasingly based on information and knowledge since the close of last century, so that questions have been raised about the changing character of classic attributes of producer-orientated services as well as to the attached relocation requirements and the changing connectivity to space in and around metropolitan regions. In the research of the Institute for Regional Development and Structural Planning (IRS) on the restructuring of the service economy of metropolitan regions, new types of producer orientated informational services were developed by analysing the change induced by ICT-technologies. Neither is their spatial association be assumed to follow the branch logic, nor can their spatial-functional interconnections be assigned to different types of metropoles. The metropoles conceived as a "global-city" or "world-city" is constituted through highly specialised services (global services) offered to headquarters of transnationals companies and international financial markets in connection with a social class who controls the process of globalisation. Although the service complex is spatially and to a large degree also functionally separated from the industrial production locations of metropolitan regions where it is physically rooted, it is crucial for the international division of labour and the ranking of cities in the global hierarchy. Will those global service economies stay partly connected to metropolitan regions through their highly ranked customers, their complex connection with other strategic producer-orientated services and the demanded urban relocation qualities? A metropolitan region can be characterised as 'technopole', when it can be related to knowledge-intensive producer-orientated services in context of reorganised value chains of the secondary sector (servindustrial economy). Modern information- and communication technologies in connection with flexible or project-orientated forms of production and distribution of goods and commodities support both, the shaping of networking technologies as well as new processes of product creation. Do informational services in those services complexes have a strong functional and spatial connection to modern decentralised production structures of metropolitan regions, and are they also embedded into innovative milieus? Related to modern ICT-technologies, the conception of an informational city conceives networks as a new structure of service economies as well as of metropolitan spatial structures. An 'informational industry' is determined by the development and location of this service complex. Does accessibility and affiliation to the 'Space of Flows' abolish traditional identity relations to real places? Can a selective connection to place of a metropolitan region be kept by knowledge holders who contribute to the informational industry? A research approach will be presented to give some answers to these questions. It is part of a interdisziplinary research project at the IRS which is called: "Metropolitan regions under the impact of the service economy: organisation, mobility and communication". The empirical base is a survey conducted in 2002 in companies working in the informational service sector in different metropolitan regions.
Keywords: 330